The stranger in the woods [compact disc, unabridged] : the extraordinary story of the last true hermit - Finkel, Michael (Books on Tape, 2017)
Documents the true story of a man who endured an isolated existence in a tent in the Maine woods, never speaking with others and surviving by stealing supplies from nearby cabins, for twenty-seven years, and illuminates the reasons behind his solitary life.